Study of the toxic effect of trichothecene mycotoxin produced by Fusarium sporotrichioides in an experiment on pigs - I. I. Idiyatov; I. R. Kadikov; V. R. Saitov; G. S. Kashevarov; I. M. Fitsev; A. M. Tremasova; K. V. Perfilova; M. M. Salnikova (Юг России: экология, развитие, 2022)
Aim. To assess the consequences of long‐term consumption by pigs of feed experimentally contaminated with T‐2 toxin in an amount close to the most commonly found in feed.Material and Methods. The experiments were carried out on pigs, which were fed food contaminated with T‐2 toxin in the amount of 200 mkg/kg for 45 days. During the experiment, the clinical condition of animals, feed and water consumption, the dynamics of live weight, analysis of blood parameters, the state of internal organs and tissues and statistical processing of the data obtained by conventional methods were undertaken.Results. Long‐term consumption of feed contaminated with mycotoxin T‐2 by pigs did not cause a pronounced clinical picture of toxicosis. However, the treated animals had diarrhea and lag in growth and development. According to the results of the blood test, it was concluded that the toxin suppressed the hematopoiesis process, inhibited protein synthesis, reduced resistance and microphagocytic function of the body, metabolic disorders and the functioning of most organs and systems. Pathological conditions and degenerative changes of cells and tissues of internal organs were recorded and mediated by the initiation of oxidative stress, inflammatory processes and cytotoxic effect.Conclusions. The consumption of feed contaminated with T‐2 toxin in a dose of 200 mkg /kg by pigs was accompanied by disturbances of metabolic processes, functions of organs and systems, manifested by a decrease in growth intensity, changes in the blood picture, activity of enzyme systems, induction of oxidative stress, immunosuppressive and inflammatory reactions and pathomorphological disorders. Thus, the oral intake of T‐2 toxin, even in small concentrations, was found to have a complex negative effect on the body.